Structural, optical and gamma radiation shielding properties of Bi₂O3/BaO-B₂O₃-TeO₂ doped CeO₂ glass system - Amat, Azuraida (2018)
Lead is one of the important elements in production of radiation shielding glass due to its high density, high atomic number and high degree of stability. However, toxicity of lead can cause negative impact to the environment and carcinogenic to human body. Three lead-free series of boro-tellurite based glass were successfully synthesized by conventional melt quenching method. These three glass compositions are: [(TeO2)70 (B2O3)30]100-x (Bi2O3)x with x = 0, 5, 10, 15, 20, 25 and 30 mol%), [(TeO2)70 (B2O3)30]100-x (BaO)x with x = 5, 10, 15, 20, 25 and 30 mol%) and {[(TeO2)70 (B2O3)30]75 (Bi2O3)25}100-y (CeO2)y with y = 1, 2, 3, 4 mol%). The effect of Bi2O3, BaO and CeO2 in boro-tellurite glasses on gamma shielding and optical properties has been studied. Gamma shielding properties measurement were conducted using “Lead equivalent thickness” equipment while optical properties were determined using UV-VIS spectrophotometer. The density measurement (Archimedes principle), amorphous phase (X-ray diffraction), structural changes (Fourier Transform Infrared (FTIR)) and theoretical calculation of parameter radiation shielding (WinXcom program) are provided for supportive evidence to gamma shielding and optical properties. The results show, the glass densities increases with the increase of Bi2O3, BaO and CeO2 content which due to the high molecular weight of glass modifier compared to glass network TeO2–B2O3. The increase in densities of glasses are also due to the increase in the number of non-bridging oxygen (NBO) atoms and the replacement of a low–density oxide B2O3 (2.46 g/cm3) and TeO2 (5.67 g/cm3) by a high–density oxide Bi2O3 (8.99 g/cm3), BaO (5.72 g/cm3) and CeO2 (7.65 g/cm3). XRD result show all glasses are amorphous in nature. The absorption peak changes shown in FTIR spectra are depended on the glass composition. FTIR analysis show the glass sample consist of TeO3, TeO4, TeO6, BO3 and BO4 structural units. The attenuation coefficients were measured for gamma ray photon energy of 662 keV. These coefficients were used to obtain the values of mass attenuation coefficients, mean free path, half value layer and effective atomic number. Results showed the shielding properties improved as increasing amount of glass modifiers (Bi2O3 and BaO). But, the shielding properties decrease with the increasing of CeO2. Results from theoretical calculation also showed that Compton scattering is a major interaction in gamma energy of 662 keV. Half value layer and mean free path of the glass systems has been compared with some standard radiation shielding materials. The [(TeO2)0.7(B2O3)0.3]0.7(Bi2O3)0.3 glasses were found to give the lowest mean free path (2.9265) and half value layer (2.0281) compared to other glass samples and even better than some standard concretes and commercial radiation shielding glasses. This indicates that [(TeO2)0.7(B2O3)0.3]0.7(Bi2O3)0.3 glass is more efficient to attenuate the 662 keV gamma ray and provides a better shielding glass. The optical band gap energy, Eg,indirect which was calculated from Tauc’ plots decreases from 3.08 to 2.78 eV and 3.49 to 3.23 with the increased amount of Bi2O3 and BaO, respectively. The shift of the absorption edge to higher wavelength are also observed. The shift of the absorption edge and decrease of Eg value attributed the restructure of glass network and modifier, and it can be related to the progressive increase in the concentration of non-bridging oxygen (NBO) atoms. The refractive indices of glass were found to increase from 1.767 to 2.093, 1.767 to 1.839 and 1.955 to 2.098 with the increase amount of Bi2O3, BaO dan CeO2, respectively. It is due to the high polarization and density of host material and glass modifier. In order to observe the ability of studied glasses against gamma irradiation, selected glass samples from each series were exposed to 60Co radioisotope to the overall dose of 45 kGy. The changes of peak intensity of FTIR spectra after exposed to gamma radiation are due to breaking of network bonding and displacement of lattice atoms. The Eg values of the glasses keep decreasing after exposed to gamma irradiation. Gamma irradiation causes the breaking up of three dimensional networks leading to the transformation of bridging oxygen (BO) to non-bridging oxygen (NBO). Negative charge from NBO have larger magnitude compared to BO. These NBO ions raise the top of the valence band resulting in the reduction of optical band gap.